Urban churches in an infrasecular landscape: three case studies from the Anglican Diocese of London. Issue 2 (3rd April 2022) - Jordan, Kate
Abstract : Church architecture is an overlooked barometer of urban life. It holds up a unique mirror to economic models, demographics, cultural and ritual practices, and aesthetic movements in late modernity. In turn, the changing complexion of secular society has had a marked influence on the type and style of Christian architecture in the twenty-first century. This article explores the dialectical relationship between church architecture and secular society within recent critical frameworks, examining, in particular, the value of infrasecular geographies as an alternative to the post-secular lens. The infrasecular model is used to frame a reading of three recently completed schemes within the Anglican Diocese of London, which have been selected to offer a snapshot of new church architecture. These comprise a purpose-built church, a refurbished Grade II* listed church, and a 'church' which operates within a custom-made boat. All three have been promoted by the Diocese of London as successful initiatives within the Church's growth strategy and all three were sufficiently high profile to be covered in the national and architectural press. In reading these churches as markers of wider shifts in the urban landscape, the article agrees with David Goodhew that, 'the many studies of modern London that airbrushed out churches (and often faith in general) present a seriously incomplete picture'.